Evidence of surface transport and weak antilocalization in a single crystal of the Bi2 Te2Se topological insulator - Shekhar, Chandra; Violbarbosa, C. E.; Yan, Binghai; Ouardi, Siham; Schnelle, W.; Fecher, Gerhard H.; Felser, Claudia (Physical Review B - Condensed Matter and Materials Physics, 2014)
Topological insulators are known for their metallic surface states, a result of strong spin-orbit coupling, that exhibit unique surface transport phenomenon. However, these surface transport phenomena are buried in the presence of metallic bulk conduction. We synthesized very high quality Bi2Te2Se single crystals by using a modified Bridgman method that possess high bulk resistivity of >20 Ωcm below 20 K, whereas the bulk is mostly inactive and surface transport dominates. The temperature dependence of resistivity follows an activation law like a gap semiconductor in temperature range 20-300 K. To extract the surface transport from that of the bulk, we designed a special measurement geometry to measure the resistance and found that single-crystal Bi2Te2Se exhibits a crossover from bulk to surface conduction at 20 K. Simultaneously, the material also shows strong evidence of weak antilocalization in magnetotransport owing to the protection against scattering by conducting surface states. This simple geometry facilitates finding evidence of surface transport in topological insulators, which are promising materials for future spintronic applications.
CRIS-Team Scopus Importer:2023-03-20